DESIGN PERFORMANCE OF BEDROOMS IN URBAN HOTELS IN ALGERIA WITH PARTICULAR REFERENCE TO FURNITURE SUITABILITY (Sciences & Technologie. D, Sciences de la terre, 2007)
As far as the Algerian context is concerned, the importance of building post-occupancy evaluation (POE)* in architecture cannot be overstressed. Evaluation of buildings is of particular importance in order to assess how well buildings match users' needs, and identifies ways to improve building design. On the other hand, the provision of design guidance based on research and evaluation is of particular importance. Many building types have guidelines for design, but few are based on adequate research and evaluation; many are too general to be of sufficient use in architectural design. A review and analysis of design guidance about bedrooms in urban hotels provided by the Ministry of Tourism does not provide adequate data for Architects. The existing guidance seems to be a standard guide with mandatory facilities and spaces. It deals mainly with the dimension of spaces with little attention to other design requirements. Accordingly, operational problems may exist since the project in use has not been designed on the basis of a clear knowledge of the market and detailed design guidance. This article aims to discover through evaluation how the completed and occupied space performs in use; to determine possible misfits, mistakes, or omissions; and to accumulate information and guidance for future programming and design efforts. It deals mainly with the performance ofbedrooms in urban hotels in Algeria. This article, will not cover all aspects of design requirements, but deals only with evaluating furniture suitability in urban hotels .